Peran Kelembagaan Pemerintah Desa dalam Memajukan Desa Ponggok-Polanharjo, Klaten - Fenita Enggraini; Nanda Cahyani Putri; Yusda Aripin Salman; Wiwandari Handayani (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2020)
Law Number 6 of 2014 concerning Villages exists to strengthen the authority of Government Village Government to regulate its own affairs as an implementation of regional autonomy. The village government is given the authority to develop their region by exploring the village potentials. Village-Owned Enterprises (BUM Desa) are present as an organization formed by the Village Government in terms of managing village assets that bring value to village income. This study aims to analyze the institutional role of the Village Government and BUM Desa in the development of the Ponggok village. The method used in this study is stakeholder analysis. This analysis was carried out to identify the roles, influences and interests of the Village Government and BUM Desa institutions. The results showed that the Village Head played role as a key player who had very strong interests and influence both in terms of the status of power, degree of organization, and personal relations to influence/involve other stakeholders for the development of Ponggok Village.